Lesbian, gay, bisexual and transgender aging adults educational guidelines to create community of care within long-term care organizations - Quigley, Jake (Kansas State University, 2011)
More than 5% of the 65 and older population utilize nursing homes, congregate care, assisted living, and board-and-care homes, with about 4.2% of these individuals occupying nursing homes at any given time (Administration on Aging, 2008). The rate of nursing home use generally increases with age and studies have shown that by the year 2030, the number of lesbian, gay, bisexual and transgender (LGBT) adults over the age of 65 is expected to be nearly 3 million (SAGE, 2010). With this overall increase in potential resident populations, those aging adults who identify as LGBT are faced with additional unique challenges commonly not encountered by their heterosexual counterparts. The majority of LGBT elders fear they will experience discrimination in long-term care organizations, with more than half maintaining that staff or even other residents will abuse or neglect them (Knochel, et al., 2010). Unrevised long-term care organizational rules combined with prejudice and hostile treatment from staff members can create unwelcoming environments for LGBT elders who are generally unable to advocate for themselves. Challenges that aging LGBT adults face in long-term care settings will be reviewed and discussed in this report. In addition, this report will provide educational guidelines to assist long-term care organizations in developing an educational model targeted at addressing LGBT elders’ concerns. When staff within a long-term care community lack proper training on and understanding of LGBT concerns, it can negatively affect the quality of care provided to these members. As such, the educational guidelines will encourage an educational model incorporating cultural competency training among the long-term care staff and organizational leadership, and will utilize community development principles to ensure inclusiveness and increase social capital.
Keywords: Lesbian, gay, bisexual, transgender; Community development; Aging adult; Educational guidelines; Gerontology (0351)